(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Chronic anal fissure is one of the most frequent proctological disorders worldwide. Closed Lateral Internal Sphincterotomy (LIS) is one of the therapeutic options accepted as the treatment of choice for Chronic Anal Fissure (CAF) as it reduces the hypertonia of the internal anal sphincter, decreases anal pain, and allows the fissure to heal. LIS can be done under general anesthesia or local anesthesia. Aim of this study was to see the post operative outcome of closed LIS done under local anaesthesia. Materials and methods : This retrospective study was conducted in Department of Surgery of Chattogram Medical College hospital and some private hospitals of Chattogram city from January 2008 to December 2017. Total 550 patients of CAF who underwent closed LIS under local anesthesia were included. Atypical fissures associated with other disease were excluded. Results: The mean duration of hospital stay was 3.38 ± 1.2 hours. Sentinel skin tag was excised in 296 patients. The fissure was posterior in 73.63% patients and anterior in 7.81% patients. Recurrence was noted in 1.3% patients within four months. 63.27% patients experienced normal continence except occasional lack of fecal control postoperatively and only one patient developed gross incontinence of solid and liquid stool. Conclusion : This study concluded that closed LIS under local anaesthesia is the procedure of choice for management of CAF as it is cost effective and time saving. JCMCTA 2018 ; 29 (2) : 53-56